Influence of Soil Modeling Uncertainties on Site Response. Issue 3 (August 2013) - Barani, Simone; De Ferrari, Roberto; Ferretti, Gabriele
The scope of this work is to examine the influence of the uncertainty in soil modeling on numerical ground response estimates through a comprehensive sensitivity analysis. This allows identification of those parameters with the largest effect on both soil amplification (quantified here by a frequency-independent factor, Fa ) and fundamental frequency, f 0 . Although extensively examined in previous articles, the effect of the input motion is also analyzed. The uncertainty affecting the shear wave velocity ( VS ) profile was found to be the factor contributing most to the uncertainty of both Fa and f 0 . The soil thickness was also found to play a key role, particularly in those cases where bedrock depth is unknown or largely uncertain. Although of secondary importance compared to the effect of VS on Fa and f 0, the influence of the input motion cannot be neglected; rather it becomes predominant with regard to the uncertainty affecting frequency-dependent shaking parameters.